Quantum Computing Technology: Towards Superfast Computational Power - Pratomo, Arief Budi; Asfahani, Asfahani; Sitopu, Joni Wilson; Salamena, Gianita Anastasia (Universitas Pahlawan Tuanku Tambusai, 2024)
Quantum computing technology is determined to revolutionize computing power by leveraging the principles of quantum mechanics. The primary issues include qubit stability, error rates, and the need for extremely low temperatures to maintain quantum coherence. This research aims to explore advances in qubit stability, quantum error correction, and hybrid quantum-classical systems to overcome current limitations in quantum computing. This research method utilizes the Systematic Literature Review (SLR) methodology. This research systematically identifies, evaluates, and synthesizes existing research. The results of this research reveal significant advances in qubit coherence times. These innovative error correction techniques integrate machine learning and practical implementation of hybrid systems while highlighting ongoing challenges in scalability and integration. This study provides recommendations for developing scalable architectures and robust integration methods to exploit the potential of quantum computing fully.